Yoga for Myocardial Infarction Care, What’s the Recommendation? - Purnamayanti, Ni Kadek Diah; Wirawan, Alfonsius Ade (Indonesian Contemporary Nursing Journal (indones.contemp.nurs.j.), 2024)
Aims: There was limited evidence of yoga involvement in caring for patients with cardiac infarction. The study aims to reveal the effect of yoga in cardiac rehabilitation post-myocardial infarction. Methods: This study is a systematic review. Literature searching was conducted in October 2023 in Google Scholar, Proquest, Sage Journal, and Pubmed databases. Inclusion criteria include clinical trials in the last five years. Exclusion criteria for a single-arm intervention.  Results: Findings included six RCTs conducted in India, Poland, and the UK. Yoga interventions varied widely, with most delivered over 12 weeks, the longest extending to a one-year follow-up and the shortest provided in a single 45-minute session. Three studies assessed echocardiographic outcomes, with two reporting improved ejection fraction and one finding no significant change. Additionally, three studies demonstrated improvement in psychosocial outcomes. Conclusion: As a potentially effective strategy, Yoga is a potential therapeutic intervention for cardiac rehabilitation programs among myocardial infarction patients.